Micro-Hydro/Solar Hybrid System Framework for Off-Grid Application - Nuramalina, Bohari; Wan Azlan, Bin Wan Zainal Abidin; Martin, Anyi; Dayang Nur Salmi Dharmiza, Awang Salleh (JASPE, 2015)
This paper introduces the conceptual system design of micro-hydro/solar hybrid system for Kampung Semulong Ulu, Sri Aman, Sarawak. Currently, Kampung Semulong Ulu is powered by solar and diesel-generator energy systems. The existing solar system generates less than 160 W for each door of the longhouse. With the completion of micro-hydro system along with the existing solar panel in the village, the community is hoping to get the proper and continuous power generation. Community in Kampung Semulong Ulu is facing difficulties since solar is only available for a limited period and yield electricity within a limited range of load. On the other hand, the running cost of diesel-generator is very expensive and unaffordable. However, even with the existence of power generated by micro-hydro system, better utilization of the energy produced is still of vital importance due to the fact that the amount of energy generated is limited. Therefore, the conceptual system design of the hydro-solar system integration is presented. The proposed system is to ensure that the energy produced will be well-distributed and at the same time, both systems must be utilized sufficiently to ensure their sustainability. In overall, this paper presents the micro-hydro/solar hybrid system framework for off-grid application toward the community in Kampung Semulong Ulu.